Structures and architecture : proceeding of the First International Conference on Structures and Architecture, ICSA 2010, Guimarães, Portugal, 21-23 July 2010 /: proceeding of the First International Conference on Structures and Architecture, ICSA 2010, Guimarães, Portugal, 21-23 July 2010. (2010) - Unknown
No abstract available